The role of emotions on consumers' satisfaction within the fitness context - Vera Pedragosa; Rui Biscaia; Abel Correia (Universidade Estadual Paulista (UNESP), 2015)
Previous studies have suggested that consumption-related emotions are important to understand post-purchase reactions. This study examines the relationship between fitness consumers' emotions and overall satisfaction. After an initial step of free-thought listing and content validity, followed by a pre-test, a survey was conducted among consumers of five different fitness centers (n=786). The questionnaire included measures to assess positive and negative emotions, as well as overall satisfaction with the fitness center. The results gathered through a structural equation model provide evidence that negative emotion experienced by consumers impacts negatively overall satisfaction, while positive emotion have a positive effect on overall satisfaction. These findings suggest managerial implications, such as the need to collect consumers' perceptions of both tangible and intangible aspects of the services, listen costumers' opinions in a regular basis, and provide regular training to staff members, in order to identify the triggers of positive emotions and contribute to increased levels of overall satisfaction. Guidelines for future research within the fitness context are also suggested.